(untitled) (Bioremediation Science and Technology Research (e-ISSN 2289-5892), 2020)
Lead (II) biosorption using Cystoseira stricta data from a previous study was used for thermodynamics investigation. Thermodynamics study of sorption is very important as it can reveal precious information regarding the spontaneity and reaction types. This study computed thermodynamics parameters for the biosorption reaction of Pb (II) by Cystoseira stricta biomass, energy change (Î”G= ï€18.74, ï€20.80, and ï€21.82 kJ/mol at 30, 35 and 40oC respectively), enthalpy change (Î”H= 75.01 kJ/mol) and entropy change (Î”S= 309.78 J/mol). The parameters were found to be spontaneous (ï€Î”G), endothermic (+Î”H) and the (+Î”S) value indicates increased randomness of the reaction. Likewise, the reaction process was found to be physical, deriving energy in the form of heat from the surrounding. Confidence interval (95%) for each of the parameter was also calculated.